The Potentials of Faecal Sludge Treatment using Local Conditioners in Tanzania: A Review - Doglas, Benjamin; Mayo, Aloyce W.; Gabrielsson, Sara; Kimwaga, Richard (Tanzania Journal of Engineering and Technology, 2020)
Worldwide, every day human beings generate millions of tons of Faecal Sludge (FS), which is rich in water, nutrients, energy, and organic compounds. Yet FS is not being managed in a way that permits us to derive value from its reuse, while at the same time, millions of farmers struggle with depleted soils and lack of water. In most of the developing countries, energy for cooking is mainly derived from cutting of trees, either as wood or charcoal. Resource recovery and reuse from FS can create livelihoods, enhance food security, support green economies, reduce waste and contribute to cost recovery in the sanitation chain. Many studies have reported on the different technologies used for FS treatment, such as dewatering and bio-stabilization. The commonly used dewatering technology is sand drying bed, which occupied a large space and has a low dewatering rate. To enhance the dewatering rate of FS as well as reducing the size of the sand drying bed, the use of chemical conditioners has been done. Despite the fact that they have been used successfully, chemical conditioners are expensive, have health and environmentally hazardous. In recent years, attempts have been made to use local conditioners to tackle the drawbacks experienced from chemical conditioners. Although the feasibility of applying local conditioners for FS dewatering has been studied, its potentials on FS treatment have not been well documented. This review indicates that there is potential for local conditioners linked with dewatering, enhancing of FS resources recovery and in reducing costs of operating and maintaining FS treatment plant. Moreover, local conditioners have the potential in contribution to socio-economic development in Tanzania through renewable energy production, income generation and food- health security, soil and water conservation, eco-sanitation and reduction of environmental degradation. Keywords: Faecal sludge, Local conditioners, Resource recovery, Sanitation, Treatment.